Anatomic and Histological Study of the Anterolateral Aspect of the Knee: A SANTI Group Investigation. Issue 10 (4th October 2018) - Daggett, Matt; Stephenson, Clark; Dobson, John; Whitaker, Amy; Redler, Andrea; Monaco, Edoardo; Wright, Barth; Saithna, Adnan; Sonnery-Cottet, Bertrand
Background: The structure and function of the anterolateral aspect of the knee have been significantly debated, with renewed interest in this topic since the description of the anterolateral ligament (ALL). Purpose: To define and describe the distinct structures of the lateral knee and to correlate the macroscopic and histologic anatomic features. Study Design: Descriptive laboratory study. Methods: Twelve fresh-frozen human cadavers were used for anatomic analysis. In the left knee, a layer-by-layer dissection and macroscopic analysis were performed. In the right knee, an en bloc specimen was obtained encompassing an area from the Gerdy tubercle to the posterior fibular head and extending proximally from the anterior aspect to the posterior aspect of the lateral femoral epicondyle. The en bloc resection was then frozen, sliced at the level of the joint line, and reviewed by a musculoskeletal pathologist. Results: Macroscopically, the lateral knee has 4 main layers overlying the capsule of the knee: the aponeurotic layer, the superficial layer including the iliotibial band (ITB), the deep fascial layer, and the ALL. Histologically, 8 of 12 specimens demonstrated 4 consistent, distinct structures: the ITB, the ALL, the lateral collateral ligament, and the meniscus. Conclusion: The lateral knee has a complex orientation of layers and fibers. The ALL is a distinct structure from the ITB and is synonymous to the previously described capsulo-osseous layer of the ITB. Clinical Relevance: Increasingly, lateral extra-articular procedures are performed at the time of anterior cruciate ligament reconstruction. Understanding the anatomic features of the anterolateral aspect of the knee is necessary to understand the biomechanics and function of the structures present and allows surgeons to attempt to replicate those anatomic characteristics when performing extra-articular reconstruction.